Islam Puritan dan Islam Moderat (Pembacaan Terhadap Kedudukan Perempuan) - Munawir, Munawir (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
The Moslem extremist -with the spirit of return to pure Islam- takes the Prophet and sahabat's period as the true Islam that oftenly they doesn't care about living Islam, in present or future. In Islamic thought spectntm, they are minority against Moslem majority. However, supporting by affluence fund, they dare shooting in the name of Gad's representative and then use many harshness on people they consider as Gad's enemy. This paper will explain about Moslem extremist appearance against Moslem moderate on women's issues.